Efficient organocatalytic route to the atorvastatin side-chain - George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An organocatalytic route to the synthesis of the atorvastatin side-chain, a building block present in the statin family, is described using L-proline-catalyzed alpha-aminooxylation of an aldehyde. The method also employs an iodine-induced intramolecular electrophilic cyclization of a carbonate to produce the iodocarbonate in a highly diastereoselective manner. (C) 2007 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone via Rh-catalyzed diastereoselective oxidative C-H aminations - Narina, Srinivasarao V.; Kumar, Talluri Siva; George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An efficient enantioselective synthesis of (-)-cytoxazone (1) and (+)-epi-eytoxazone (2) using proline-catalyzed asymmetric alpha-amino-oxylation of aldehydes followed by Rh-catalyzed diastereoselective oxidative C-H amination as the key steps is described. syn or anti 1,2-aminoalcohols were obtained by Rh-catalyzed intramolecular amidation of the C-H bonds of carbamates or sulfamate esters with good to excellent diastereoselectivity. (c) 2006 Elsevier Ltd. All rights reserved.

Enantioselective synthesis of tarchonanthuslactone using proline-catalyzed asymmetric alpha-aminooxylation - George, Shyla; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2007)
A practical enantio selective synthesis of tarchonanthuslactone 1, an important natural product with a polyol unit, is described. The sequence of synthetic reactions involves proline-catalyzed alpha-aminooxylation and iodine-induced electrophilic cyclization as the chiral inducing steps. (c) 2007 Elsevier Ltd. All rights reserved.